2022
DOI: 10.1515/epoly-2022-0090
|View full text |Cite
|
Sign up to set email alerts
|

Thyme/garlic essential oils loaded chitosan–alginate nanocomposite: Characterization and antibacterial activities

Abstract: For controlling pathogenic bacteria using nanopolymer composites with essential oils, the formulation of chitosan/alginate nanocomposites (CS/ALG NCs) loaded with thyme oil, garlic oil, and thyme/garlic oil was investigated. Oils were encapsulated in CS/ALG NCs through oil-in-water emulsification and ionic gelation. The CS/ALG NCs loaded with oils of garlic, thyme, and garlic–thyme complex had mean diameters of 143.8, 173.9, and 203.4 nm, respectively. They had spherical, smooth surfaces, and zeta potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Jabir et al [65] fabricated gold nanoparticles modified with glutathione and linalool and reported a MIC for E. coli bacteria of 0.77 µg mL −1 and 1.54 µg mL −1 for S. aureus. Elghobashy et al [66] elaborated on chitosan nanocomposites with alginate loaded with thyme and essential garlic oil and showed that the bactericidal efficacy of essential oils improved when these were combined, the MIC obtained for E. coli was 15 µg mL −1 , while for S. aureus it was 7.5 µg mL −1 , and these values were lower than those obtained. We can say that essential oils are effective against the inhibition of Gram-positive and Gram-negative bacteria when transferred to other materials.…”
Section: Microbiological Testsmentioning
confidence: 99%
“…Jabir et al [65] fabricated gold nanoparticles modified with glutathione and linalool and reported a MIC for E. coli bacteria of 0.77 µg mL −1 and 1.54 µg mL −1 for S. aureus. Elghobashy et al [66] elaborated on chitosan nanocomposites with alginate loaded with thyme and essential garlic oil and showed that the bactericidal efficacy of essential oils improved when these were combined, the MIC obtained for E. coli was 15 µg mL −1 , while for S. aureus it was 7.5 µg mL −1 , and these values were lower than those obtained. We can say that essential oils are effective against the inhibition of Gram-positive and Gram-negative bacteria when transferred to other materials.…”
Section: Microbiological Testsmentioning
confidence: 99%
“…Particularly for organic substituents like oils, a more suitable approach involves formulating them using the oil-in-water emulsification method, followed by combining them with ionic gelation. 106 , 124 , 127 , 130 , 133 This method not only enhances the encapsulation of oils but also improves the stability of the active ingredients, preventing their premature release during storage.…”
Section: Evidence Of Antibacterial Agents’ Delivery Using Chitosan/al...mentioning
confidence: 99%
“… [ 129 ] Thyme essential oil (TEO) and garlic essential oil (GEO) Oil-in-water emulsification combined with ionic gelation method In vitro Staphylococcus aureus, Escherichia coli , and Aeromonas hydrophila MIC (in S. aureus ): TEO-loaded NPs = 10 µg/mL GEO-loaded NPs = 12.5 µg/mL TEO-GEO-loaded NPs = 7.5 µg/mL Chitosan components, besides serving as nanostructure formers, also provide a synergistic effect through interactions with essential minerals on bacteria and forming a film on the bacterial surface, preventing nutrient entry into bacterial cells. [ 130 ] Grape pomace extract Ionic gelation method In vitro Methicillin-susceptible Staphylococcus aureus (MSSA), Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis , and Listeria monocytogenes Encapsulation of grape pomace extract into NPs exhibit highest bacterial reduction against MMSA: 5-log reduction (higher than raw extract, 3-log reduction) The use of encapsulation systems into chitosan and alginate provides protection effects for antibiotic components in the extract (anthocyanins and neochlorogenic acid), thus enabling antibacterial effects even upon delivery to the intestines. [ 131 ] Artocarpus lacucha Roxb.…”
Section: Evidence Of Antibacterial Agents’ Delivery Using Chitosan/al...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Elghobashy et al [ 149 ] conducted a study where they developed a chitosan/alginate nanocomposite loaded with thyme and garlic EOs. The researchers fabricated NPs using this composite and loaded them with the EOs, resulting in particles ranging from 150 to 200 nm in size and possessing a Z-potential of approximately 30 mV.…”
Section: Other Nanostructured Systems For Eos Deliverymentioning
confidence: 99%